NOT EVERY CELL IS SACRED: A REPLY TO CHARO - Disilvestro, Russell (Bioethics, 2006)
Massimo Reichlin, in an earlier article in this journal, defended a version of the ‘argument from potential’ (AFP), which concludes that the human embryo should be protected from the moment of conception. But R. Alta Charo, in her essay entitled ‘Every Cell is Sacred: Logical Consequences of the Argument from Potential in the Age of Cloning’, claims that versions of the AFP like Reichlin’s are vulnerable to a rather embarrassing problem: with the advent of human cloning, such versions of the AFP entail that every somatic cell in the human body ought to be protected. Since this entailment is clearly absurd, Charo argues, these versions of the AFP should be rejected. I argue that the reasons Charo cites for believing in this entailment are inconclusive. For example, the four reasons she gives for doubting any differences between the nature of skin cells and zygotes are ultimately unconvincing. Against Charo, I maintain that there is a relevant distinction between the sort of potential possessed by the somatic cell and the sort of potential possessed by the early human embryo. Since only the latter sort of potential falls within the scope of the AFP, the alleged absurd entailment Charo invites us to consider is no entailment at all. Hence the AFP cannot be rejected on the grounds Charo advances. Even in an age of cloning, the claim that some cells are ‘sacred’ because of their potential does not entail the claim that every cell is sacred.